Assessing the robustness of carbonate‐associated sulfate during hydrothermal dolomitization of the Latemar platform, Italy. (12th September 2021) - Schurr, Simon Lukas; Strauss, Harald; Mueller, Mathias; Immenhauser, Adrian
Abstract: Carbonate‐associated sulfate (CAS) is an important proxy for reconstructing marine sulfur cycling throughout Earth's history. In order to assess the impact of carbonate neomorphism on δ 34 SCAS data, a mineralogical‐spatial transect from early diagenetic limestone into low‐temperature hydrothermal dolostone was analyzed in the middle Triassic Latemar platform interior, northern Italy. This study addresses the yet unconstrained question whether hydrothermal dolostone preserves a marine δ 34 SCAS signature and, hence, might represent an archive for past seawater sulfate. In this study, δ 34 SCAS values were measured in low‐temperature hydrothermal dolostone and compared with data from their corresponding precursor limestone. Results shown here reveal that δ 34 SCAS values for dolostone and precursor limestone are indistinguishable. This points to a rock‐buffered middle Triassic marine δ 34 S signature not affected by hydrothermal alteration. Hence, hydrothermal dolostone represents, under favorable conditions, an archive for unraveling past marine sulfur cycling.